Sources of Growth - David Audretsch; Roy Thurik (Tinbergen Institute, 1997)
The purpose of this paper is to suggest that a fundamental shift in Europe, along with the other OECD countries, is taking place. This shift is from the managed economy to the entrepreneurial economy. While politicians and policy makers have made a plea for guidance in the era of entrepreneurship,scholars have been slow to respond. The purpose of this paper is to make a first step identifying and articulating these differences. We do this by contrasting the most fundamental elements of the newly emerging entrepreneurial economy with those of the managed economy. We identify fifteen trade-offs confronting these two polar worlds. The common thread throughout these trade-offs is the increased role of new and small enterprises in the entrepreneurial economy. A particular emphasis is placed on changes in economic policy demanded by the entrepreneurial economy vis-à-vis the managed economy. We then explore whether restructuring towards the entrepreneurial economy has been conducive to economic growth and job creation. Our empirical analysis links the stage of the transition towards an entrepreneurial economy to the growth rates of European countries over a recent period. We find that those countries which have introduced a greater element of entrepreneurship have been rewarded with additional growth.
Keywords: O0; L0; 330